The Politics of Transformative Feminist Adult Education: Multi-Centred Creation of New Meanings and New Realities - Angela Miles; Phyllis Cunningham; Miriam Zukas; Kamla Bhasin; Jean Graveline; Mechthild Hart; Vanessa Sheared; Jane Thompson; Sally Westwood (Adult Education Research Conference, 2000)
No abstract available.